1980
DOI: 10.1021/es60162a001
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of pentachlorophenol-treated wood. Chlorinated dibenzo-p-dioxin formation

Abstract: single-time assays of trihalomethanes in drinking water. Furthermore, there is sufficient variation in even a large system so that a simple harmonic model cannot allow prediction of trihalomethane concentrations from one day to the next. If a maximum contaminant level for these compounds in drinking water is to be monitored, recognition of the 24-h variation is essential, but in addition the larger contribution of as yet undefined sources of day-to-day variability must be taken into account. The observed day-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…It also has been proved that the irradiation of several PCPcontaining aqueous solutions indicated the formation of higher chlorinated PCDD/Fs (Vollmuth et al, 1994). Laboratory studies have been conducted to determine the effect of sunlight on the concentrations of PCP and PCDDs in wood treated with PCP (Lamparski and Stehl, 1980). However, few studies on the phototransformation of PCDDs via photolysis of PCP on soils surface have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It also has been proved that the irradiation of several PCPcontaining aqueous solutions indicated the formation of higher chlorinated PCDD/Fs (Vollmuth et al, 1994). Laboratory studies have been conducted to determine the effect of sunlight on the concentrations of PCP and PCDDs in wood treated with PCP (Lamparski and Stehl, 1980). However, few studies on the phototransformation of PCDDs via photolysis of PCP on soils surface have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…70ppm for the two artificial sunlight exposures. 18 Moreover, in the case of Dow pentachlorophenol (16), the equilibrium concentration of H 7 CDDs were 35 and 35ppm, while those of H 6 CDDs were 10.5 and llppm for both artificial and natural sunlight, respectively. 18 It is noteworthy that methylene chloride was used as carrier solvent for Reaction 10.…”
Section: Photoformation Of Polychloriimated Dibenzo-p-dioxins (Pcdds)mentioning
confidence: 94%
“…18 Moreover, in the case of Dow pentachlorophenol (16), the equilibrium concentration of H 7 CDDs were 35 and 35ppm, while those of H 6 CDDs were 10.5 and llppm for both artificial and natural sunlight, respectively. 18 It is noteworthy that methylene chloride was used as carrier solvent for Reaction 10. According to Lamparski and his associates, 18 most of the hexa-and heptachloroisomers of PCDDs were generated through photodegradation of O 8 CDD (17) rather than by condensation of tetrachlorophenols and 16.…”
Section: Photoformation Of Polychloriimated Dibenzo-p-dioxins (Pcdds)mentioning
confidence: 94%
“…Several authors have reported solution phase as well as solid phase environmental photochemistry of P5CP (1) (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Recently, we (22) have reported our investigations on the environmental photochemistry of several PCPs, namely tetra-and pentachlorophenols in H20-CH3CN (2:3 v/v) at A r 290 nm concluding that the process of reductive 'For Part VII, see ref.…”
Section: Introductionmentioning
confidence: 92%